The Effect of Phytobiotics Supplementation and Magnetized Drinking Water on Production Performance and Egg Quality of Laying Hens (Jurnal Ilmu dan Teknologi Hasil Ternak, 2021)
The experiment was conducted to evaluate the production performance and egg quality of laying hens supplemented with phytobiotics and magnetized drinking water. This experiment used 2700 gauss level in Magnetized Drinking Water (MDW). The phytobiotics had two form: the non-encapsulated phytobiotics (PTO) and encapsulated phytobiotics (EPTO). There were untreated water (control) and the treated water (MDW, PTO, PTO+MDW, EPTO, EPTO+MDW). The treatments were presented by 0.6% for each treatment. The result showed highly significant (p<0.01) improvement on feed conversion ratio (FCR) but no significant effect on other production performance variables including feed intake, hen day production (HDP), egg mass, and income over feed cost (IOFC). The results indicated a highly significant improvement (p<0.01) on egg weight and yolk cholesterol. There were no significant effects on shape index (SI), shell weight, shell thickness, Haugh unit (HU), albumen height, yolk weight, yolk index (YI), and yolk color of egg quality variables. It was concluded that the encapsulated form (EPTO and EPTO+MDW) had the best improvement on FCR and yolk cholesterol, on another hand the non-encapsulated form (PTO and PTO+MDW) increased the egg weight of laying hens